Projeto de “artesãs empreendedoras”: trajetórias de mulheres em um programa de inserção produtiva - Tomaz, Mariana Amaral (2016)
This thesis maps and interprets women’s trajectories, which participate in a social project called Vitrine Social, which goal is to generate income. The aim is to understand values, relationships and conflicts experienced during training, production and commercialization of the handcrafts. This research is centred on life trajectories of four women, who were participants of the Vitrine Social in Curitiba, Paraná, Brazil, from 2010 to 2015 and sold their products in Curitiba’s handicraft fairs, mainly at Largo da Ordem and Praça Osório Fairs. From a gender perspective, we present conflicts experienced in the process of becoming a “handcraft-businesswoman”, since this program proposes to form entrepreneurs. The methodological procedures performed on this qualitative research were participative observation of handicraft fairs, records on field diaries and life history interviews with participants from latest groups of Vitrine Social. Interviews were guided starting from handcrafts made during the course: patchwork bedspreads sewed by groups, sewing portfolios and other stitched products. In dialogue with conversationalist narratives and memories we attempted to build an image of the whole process: the decision of taking part of the course, the learning process of sewing, the business management, the formation of a productive group (and of a “Project” collective), commercialization in craft fairs, the new product development, and at last, the production at home. Looking carefully at relationships and spaces involved in each stage, it was possible to evidence inhomogeneity in the learning process, development and production of sewed handcrafts.